perancangan Perancangan Sistem E-Raport SMP Negeri 7 Bontang Berbasis Website - Lapu tombilayuk; Bagas Briliantama (STTI Bontang, 2022)
In the current era of technological development, it is commonplace to use technology in various fields of work. In the current topic, the use of technology is applied in the field of education. The role of technology in carrying out educational activities is as a medium of learning for students and doing academic work as teachers and staff. Within the school environment, SMP Negeri 7 Bontang has various activities carried out such as teaching, learning, data management, and various general activities in other schools. Therefore, we need a website-based e-raport system to manage academic information such as grades, schedules, attendance, subjects, reports, and so on. This system is also equipped with the final value calculation automatically after inputting the value. The design of this system uses the SDLC (System Development Life Cyrcle) method, by analyzing the PIECES method (Performance, Information, Economic, Control, Efficiency, Service) and testing the system using the Black Box method. The test results show that the system runs as expected at the beginning.